2016
DOI: 10.4209/aaqr.2015.09.0537
|View full text |Cite
|
Sign up to set email alerts
|

Source Apportionment of Urban Background Particulate Matter in Birmingham, United Kingdom Using a Mass Closure Model

Abstract: Particulate matter (PM) collected during the summer period of 2011 at the urban background of Elms Road Observatory Site (EROS) in Birmingham, United Kingdom was studied and apportioned using the mass closure model. Particulate matter samples were analysed for Cu, Zn, Fe, Ni, Mn, Cl -, NO 3 -, SO 4 2-, PO 4 3-, C 2 O 4 2-, Na + , NH 4 + , K + , Ca 2+ , OC and EC using the standard procedures. Results showed mean mass concentrations of 5.42 ± 1.7 µg m -3 for PM 2.5 and 5.41 ± 0.27 µg m -3 for PM 10-2.5 . Organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Nevertheless, aeolian dust contributed to 17.8-20.5% of PM 10 on the right bank and 12.3-14.3% on the left bank of the Kaoping River after the ADE (Stage II). The results indicated that a small amount of finer aeolian dust emitted from the bare lands could be still suspended in the ambient air during the period of Stage II (Lin et al, 2007;Kuo et al, 2010;Taiwo et al, 2016). Additionally, the mass percentages of sea salts obtained from sites KA and PD were always higher than other sites during the ADE.…”
Section: Source Apportionment Of Pm 10 On Regular Days and During Andmentioning
confidence: 66%
See 2 more Smart Citations
“…Nevertheless, aeolian dust contributed to 17.8-20.5% of PM 10 on the right bank and 12.3-14.3% on the left bank of the Kaoping River after the ADE (Stage II). The results indicated that a small amount of finer aeolian dust emitted from the bare lands could be still suspended in the ambient air during the period of Stage II (Lin et al, 2007;Kuo et al, 2010;Taiwo et al, 2016). Additionally, the mass percentages of sea salts obtained from sites KA and PD were always higher than other sites during the ADE.…”
Section: Source Apportionment Of Pm 10 On Regular Days and During Andmentioning
confidence: 66%
“…Previous studies reported that source identification and apportioning of PM had been recognized as one of the curial measures to quantify the major contributors of PM to improve the poor particulate air quality (Cao et al, 2009;Nayebare et al, 2016;Taiwo et al, 2016). Studies have used several measures to assess the comparative performance of various source apportionment techniques namely, CMB receptor modelling, positive matrix factorization, principal component analysis (PCA), absolute principal component analysis, and targeted factor analysis (Hopke et al, 2006;Brook et al, 2007;Nayebare et al, 2016).…”
Section: Chemical Mass Balanced (Cmb) Receptor Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, sources and factors influencing aerosol levels must be well analyzed and controlled. Particle composition in Birmingham, clearly revealed an urban aerosol profile made up by combustion generated carbonaceous particles, secondary sulphates and nitrates from regional transport and predominantly coarse (PM COARSE = PM 10 -PM 2.5 ) dusts (Harrison et al, 2004;Taiwo, 2016). Non-exhaust particles derived from tire wear and break friction, also constitute an important source of PM in Birmingham, according to Pant et al (2015); Taiwo et al (2014) and Harrison et al (2003).…”
Section: Introductionmentioning
confidence: 99%
“…However, individual contributions of each source category to PM cannot be measured directly (Shen et al, 2014). Therefore, various source apportionment methods have been developed and applied (Zheng et al, 2011;Shen et al, 2014;Taiwo, 2016;Vu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%